“CityQuest,” A Custom-Designed Serious Game, Enhances Spatial Memory Performance in Older Adults - Merriman, Niamh A.; Roudaia, Eugenie; Ondřej, Jan; Romagnoli, Matteo; Orvieto, Ivan; O’Sullivan, Carol; Newell, Fiona N. (Frontiers in Aging Neuroscience, 2022)
Spatial cognition is known to decline with ageing. However, little is known about whether training can reduce or eliminate age-related deficits in spatial memory. We investigated whether a custom-designed video game involving spatial navigation, obstacle avoidance, and balance control would improve spatial memory in older adults. Specifically, 56 healthy adults aged 65 to 84 years received 10 sessions of multicomponent video game training, based on a virtual cityscape, over five weeks. Participants were allocated to one of three training conditions: the main intervention, the ‘CityQuest’ group (n=19), and two control groups, spatial navigation without obstacle avoidance (‘Spatial Navigation-only’ group, n=21) and obstacle avoidance without spatial navigation (‘Obstacles-only’ group, n=15). Performance on object recognition, egocentric and allocentric spatial memory (incorporating direction judgement tasks and landmark location tasks, respectively), navigation strategy preference, and executive functioning was assessed in pre- and post-intervention sessions. The results showed an overall benefit on performance in a number of spatial memory measures and executive function for participants who received spatial navigation training, particularly the CityQuest group, who also showed significant improvement on the landmark location task. However, there was no evidence of a shift from egocentric to allocentric strategy preference. We conclude that spatial memory in healthy older participants is amenable to improvement with training over a short term. Moreover, technology based on age-appropriate, multicomponent video games may play a key role in cognitive training in older adults.